The Impact of Relationship Marketing On Customer Loyalty in Malaysian Banks - Zhou, Ruijie (2012)
With a high competition in service market, firms seek to find the best way to create their loyalty customers. Then many service providers, especially banks, use relationship marketing as a strategic approach to maintain long-term relationship with customers. By conducting long-term relationship with customers, banks can identify and improve important and valuable activities, thus attracting more customers. By conducting customer loyalty with banks, banks can subsequently improve their position in current competitive market. In Malaysia, banks can compete against one another as it practices open enterprise policy, thus relationship marketing is critical important for Malaysian banks to gain competitive advantages. Therefore, this research aims to examine the impact of relationship marketing on customer loyalty in Malaysian banks. There are six dimensions (Trust, Competence, Commitment, Conflict Handling, Communication and Empathy) of relationship marketing which examine the relationship with customer loyalty. Reliability Analysis, Correlation Analysis and Multiple Analysis were used to examine the relationship between dimensions of relationship marketing and customer loyalty. Moreover, the self-administration questionnaires were distributed to 250 Malaysian bank customers who were above 18 years old and had bank experience at least 1-3 times per month in Negeri Sembilan using convenience sampling method. In addition, the findings show that Trust, Competence, Commitment, Conflict Handling and Empathy have significant positive relationship with customer loyalty. Finally, recommendations are given to the people who are interested in this topic and for future researchers.